TAKING INTO ACCOUNT THE ETHNOCULTURAL CHARACTERISTICS OF STUDENTS FROM MUSLIM COUNTRIES WHILE DEVELOPING AN RFL COURSE WITH ELEMENTS OF ARTIFICIAL INTELLIGENCE (Proceedings of Southern Federal University. Philology, 2024)
DOI 10.18522/1995-0640-2024-4-187-197The use of artificial intelligence for adapting the course of Russian as a foreign language is under the analysis, that allows taking into account the individual needs and level of training of students. The advantages and challenges associated with the introduction of artificial intelligence into the educational process in the context of the ethnocultural characteristics of students are analyzed. Describes religious differences among students studying Russian as a foreign language and their attitude towards artificial intelligence. The respondent was the OpenAI ChatGPT-4 product.Key words: Russian as a foreign language, ethnocultural aspects, Muslim students, artificial intelligence, ChatGPT-4